Functional Status of the Cardiovascular System in Patients with Acute Myeloblastic Leukemia: Results of a Retrospective Study - Feruza Haydarovna, Mamatkulova; Dilafruz Abdikhalimovna , Amerova X; Qodir Ergashevich , Shomurodov (Miasto Przyszłości, 2023)
A retrospective analysis of indicators of the functional state of the cardiovascular system in patients with acute myeloblastic leukemia was conducted in the hematology center of the multidisciplinary medical center of Samarkand city. The purpose of the study: to evaluate the functional changes in the cardiovascular system in Acute myeloblastic leukemia in order to identify characteristic diseases that require preventive therapy to reduce the risk of developing the disease.